Impact of Steel Fibers and Carbon Nanotubes on the Strength and Quality of Cementitious Composites - Nikolaos Chousidis (Construction Materials)
This study examines the effects of steel fibers (SF) and carbon nanotubes (CNTs) on the performance of cementitious composites. Three types of mixes were analyzed: a reference mix (REF), a steel fiber-reinforced concrete (SFRC), and a hybrid mix containing both CNTs and SFs. The investigation included physicomechanical property evaluations, microstructural analysis, and ultrasonic pulse velocity (UPV) tests. Results indicate significant improvements in performance across the mixes, with the hybrid mix achieving the highest flexural and compressive strengths, highlighting a synergistic interaction between CNTs and SF to enhance load-bearing capacity. Additionally, the mixtures displayed reduced porosity and water absorption, signifying improved density and lower permeability. SEM analysis further confirmed a denser microstructure with enhanced crack-bridging capabilities due to the presence of CNTs and SF. UPV measurements supported these findings, demonstrating superior internal integrity and stiffness in the hybrid mix. These experimental results underscore the potential of hybrid reinforcement strategies for producing high-performance fiber concrete with enhanced durability, making it suitable for demanding construction applications.